Use of high performance computing in the assessment of congestion charging in the Greater Dublin Area - O'Cearbhaill, Eoin Alexander (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2004)
Traffic demand management is part of the package of measures currently being implemented to offset the imbalance between transport demand and supply on the transportation network of the Greater Dublin Area (GDA). An analysis of the development of the transport environment in the GDA leads to the conclusion that the transportation deficit that exists in the GDA can only be addressed using an integrated transportation strategy involving infrastructural and service improvements on one side and a demand management strategy on the other. This transportation deficit has resulted from delays in infrastructure projects and unrealistic planning targets due to institutional and regulatory inefficiencies, cumbersome and time consuming planning system, and, the high economic growth since the Dublin Transportation Initiative began in 1988.
Keywords: Civil Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin